Groundwater characterization in arid regions using seismic and gravity attributes: Al Jaww Plain, UAE - Bruno, Pier Paolo G.; Vesnaver, Aldo (Frontiers in Earth Science, 2021)
This paper discusses a multivariate approach aimed at geophysical characterization of subsurface rocks for groundwater exploration in arid environments. We integrate several findings obtained from a single-source, single-sensor seismic profile with gravity data to detail the tectonic settings and characterize the subsurface, water-bearing formations of the Al Jaww Plain, one of the most important groundwater reserves of the United Arab Emirates. The seismic data have been acquired in the framework of the first EAGE Middle-East Bootcamp. Edge-detection techniques applied to the Bouguer anomaly map of the Al Jaww Plain allowed us to infer the presence of unreported ENE trending tectonic lineaments. The prestack depth migrated seismic image shows a clear and previously unreported east-verging thrust affecting seismic wave propagation and consistent with gravity data which was interpreted as an evidence of a detachment fold and thrust above the bottom of Fiqa Formation. Using the first-arrival picking from the common shot gathers, we tested a coupled tomographic inversion of P-wave velocity and Q factor which was aimed at achieving a qualitative characterization of rock petrophysical properties. K-means clustering was used to classify and map subsurface areas characterized by similar observations of P- and Q-wave velocity and therefore to outline shallow zones (<600 m) that are consistent with geophysical properties which are typical for water accumulations and within the reach of water groundwater exploration.